2015
DOI: 10.3389/fnhum.2015.00403
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of neurostimulation and priming on creative thinking. A preliminary tDCS study on dorsolateral prefrontal cortex

Abstract: The role of prefrontal cortex (PFC) in influencing creative thinking has been investigated by many researchers who, while succeeding in proving an effective involvement of PFC, reported suggestive but sometimes conflicting results. In order to better understand the relationships between creative thinking and brain activation in a more specific area of the PFC, we explored the role of dorsolateral PFC (DLPFC). We devised an experimental protocol using transcranial direct-current stimulation (tDCS). The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 86 publications
(123 reference statements)
3
52
0
1
Order By: Relevance
“…For example, using noninvasive brain stimulation, Mayseless and Shamay‐Tsoory () reported that decreasing the activity in the left frontal parts of the brain and increasing activity in the right frontal parts of the brain—a brain modulation supposed to reduce cognitive control—have a positive effect on creative ideas production. In sharp contrast with this finding, another noninvasive brain stimulation study reported that a hyperactivation of the prefrontal cortex was beneficial for creative production, suggesting that better cognitive control led to better creative ideas generation (Colombo, Bartesaghi, Simonelli, & Antonietti, ). In a similar vein, numerous studies on clinical disorders associated with inhibitory control deficits suggest that impaired cognitive control might facilitate original associations and stimulate creative ideas generation (see de Souza et al., ).…”
Section: Limitationsmentioning
confidence: 92%
“…For example, using noninvasive brain stimulation, Mayseless and Shamay‐Tsoory () reported that decreasing the activity in the left frontal parts of the brain and increasing activity in the right frontal parts of the brain—a brain modulation supposed to reduce cognitive control—have a positive effect on creative ideas production. In sharp contrast with this finding, another noninvasive brain stimulation study reported that a hyperactivation of the prefrontal cortex was beneficial for creative production, suggesting that better cognitive control led to better creative ideas generation (Colombo, Bartesaghi, Simonelli, & Antonietti, ). In a similar vein, numerous studies on clinical disorders associated with inhibitory control deficits suggest that impaired cognitive control might facilitate original associations and stimulate creative ideas generation (see de Souza et al., ).…”
Section: Limitationsmentioning
confidence: 92%
“…However, pairing the same stimulation design with explicit instructions to visualize using an object in an unusual, relative to its typical, way significantly elevated AUT total creativity scores (Colombo et al, 2015). In line with the findings of Green et al (2017), these results demonstrate that when participants deliberately search for more creative or unusual responses the need for selectivity is amplified.…”
Section: Creative Idea Selectionmentioning
confidence: 99%
“…Additional evidence of verbal convergent thinking improvement after anodal stimulation over the left DLPFC came from the study carried out by Zmigrod et al 15 , who reported significantly better performance in a similar version of the RAT (Compound Remote Associates Task) 16 . Colombo et al 17 additionally found a significant improvement in verbal divergent thinking (alternate uses task), but only after priming on creative thinking. This last finding suggests that stimulation of the left DLPFC may also induce higher divergent thinking scores by asking participants to deliberately search for more unusual answers.…”
mentioning
confidence: 93%